2017
DOI: 10.1108/jkm-02-2017-0084
|View full text |Cite
|
Sign up to set email alerts
|

The influence of knowledge absorptive capacity on shared value creation in social enterprises

Abstract: Purpose In downturns, social enterprises (SEs) arise as a resilience business model. The authors focus on knowledge absorptive capacity (KAC) as a key dynamic capability to create shared value (SHV). The purpose of this study is to analyze whether it exists a cause-effect relationship between KAC and SHV creation in SEs. Design/methodology/approach The research model relates KAC and SHV creation. SHV creation involves two components: economic value (EV) and social value (SV). The authors argue that KAC has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 95 publications
(154 reference statements)
2
23
0
Order By: Relevance
“…Another study has highlighted the role of an individual's spiritual practices that enhance consciousness, which can play a vital role in creating a conscious enterprise that focuses on creating shared value (Pavlovich & Corner, 2014). Campos‐Climent and Sanchis‐Palacio (2017) conducted research on 127 social enterprises from France and Spain. They found that knowledge absorptive capacity (KAC) is a key determinant for creating shared value.…”
Section: The Three Main Research Streams On Csvmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study has highlighted the role of an individual's spiritual practices that enhance consciousness, which can play a vital role in creating a conscious enterprise that focuses on creating shared value (Pavlovich & Corner, 2014). Campos‐Climent and Sanchis‐Palacio (2017) conducted research on 127 social enterprises from France and Spain. They found that knowledge absorptive capacity (KAC) is a key determinant for creating shared value.…”
Section: The Three Main Research Streams On Csvmentioning
confidence: 99%
“…They found that knowledge absorptive capacity (KAC) is a key determinant for creating shared value. They argue that creating KAC acts as a mediator and positively affects CSV (Campos‐Climent & Sanchis‐Palacio, 2017). Recently, Wu et al.…”
Section: The Three Main Research Streams On Csvmentioning
confidence: 99%
“…), and factors associated to and affecting sustainable innovation, a systematization of extant findings is required to improve our knowledge regarding how firms can improve financial performance while developing a sustainable society (Campos-Climent & Sanchis-Palacio, 2017;Carayannis et al, 2017;Del Del Giudice & Straub, 2011;Malone & Yohe, 2002;Porter & Kramer, 2007). ), and factors associated to and affecting sustainable innovation, a systematization of extant findings is required to improve our knowledge regarding how firms can improve financial performance while developing a sustainable society (Campos-Climent & Sanchis-Palacio, 2017;Carayannis et al, 2017;Del Del Giudice & Straub, 2011;Malone & Yohe, 2002;Porter & Kramer, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, given the heterogeneity of topics, perspectives (strategic management, relational view, stakeholder engagement, etc. ), and factors associated to and affecting sustainable innovation, a systematization of extant findings is required to improve our knowledge regarding how firms can improve financial performance while developing a sustainable society (Campos-Climent & Sanchis-Palacio, 2017;Carayannis et al, 2017;Del Del Giudice & Straub, 2011;Malone & Yohe, 2002;Porter & Kramer, 2007). Therefore, the main aim of this study is to systematically identify and critically review the literature on sustainable innovation in order to synthesize and classify recurrent challenges and prevalent practices and thereby reconcile economic, environmental, and social goals in innovation activities.…”
Section: Introductionmentioning
confidence: 99%
“…In the social entrepreneurship sector, individual barriers like time constraints, technical barriers such as the ones associated with organisational intranet and organisational barriers such as the lack of opportunities and training, limit knowledge sharing. Further, in the field of social entrepreneurship, it has been shown by Campos-Climent and Sanchis-Palacio (2017) that the capacity for knowledge absorption positively impacts the creation of shared value in social enterprises in the euro-Mediterranean region. Through the analysis of North American social entrepreneurship education programmes, Solomon et al (2019) highlighted the potential of the knowledge management field and courses in social entrepreneurship education, which present a continuously high demand in the US and Canada, where it continues to rise.…”
Section: Findings From the Literature Reviewmentioning
confidence: 99%